Towards a cooperative question-answering model - de Sena, Galeno J. [UNESP]; Furtado, Antonio L. (Springer Nature, 1998)
A model of question-answering is proposed in this paper. In the model, the system tries, from an input query, to establish a controlled dialogue with its user. In the dialogue, the system tries to identify and to suggest to the user new queries, related to the input query. The dialogue control is based on the structure of the concepts stored in the knowledge base, on domain restrictions, and on specific constraining rules. The system kernel is essentially an extended version of a cooperative interface for accessing data and knowledge bases.